Finite Field Arithmetic Using AVX-512 For Isogeny-Based Cryptography - Orisaka, Gabriell; Aranha, Diego F.; López, Julio (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2018)
Isogeny-based cryptography introduces new candidates to quantum-resistant cryptographic protocols. The cost of finite field arithmetic dominates the cost of isogeny-based cryptosystems. In this work, we apply AVX-512 vector instructions to accelerate the finite field modular multiplication. We benchmark our implementation on a Skylake-X processor and discuss the applicability of our contribution and the directions for future work.